Evaluation of degree of correction by anterograde calcaneo-stop method in the management of juvenile flexible flatfoot: a retrospective study - Gennadiy, Koshman A.; Direcksze, Naveen D. K. N.; Yogarajah, Kirisayon; Yohanathan, Narendiran; Afham, M. N. M.; Ahmath, A. N. Nafas; Mohamed, U. M. Makarim; Wijesooriya, Heshan T. (International Surgery Journal, 2025)
Background: Flexible flatfoot is a frequent foot deformity among pediatric population. The anterograde calcaneo-stop method (ACSM) has been published to be beneficial in short-term studies. The purpose of this study to assess the degree of correction following the ACSM in the management of juvenile flexible flatfoot. Methods: The retrospective study consists of 400 surgical procedures performed from the period of January 2013 to December 2023 in 100 patients (200 ACSM and 200 removal of calcaneo-stop implant surgeries), which were evaluated clinically, and instrumental diagnostic techniques such as photoplantography and pedobarography were implemented. The inclusion criteria of this study comprises of patients with ages from 6 to 16 years,with symptomatic flexible flatfoot deformity along with absence of responsive to bilateral conservative treatment and the exclusion criteria includes the following; patients with ages below 6 years and above 16 years, the time ceased of 3 years after screw implantation, patients with other musculoskeletal deformities. Results: The 200 surgical interventions performed on bilateral flexible flatfoot were evaluated in 100 patients after their removal of the screws following the ACSM, showed no signs of loss of degree of correction; which were further evaluated by degree of connective tissue dysplasia according to Wynne-Davies, radiologically by photoplantography and pedobarography. Conclusions: The ACSM is a simple surgical treatment, which is minimally invasive in nature used for symptomatic juvenile flexible flatfoot. The collected data stipulated a sufficient degree of correction by ACSM in the management of flexible flatfoot in the pediatric population.